2013
DOI: 10.1371/journal.pone.0076560
|View full text |Cite
|
Sign up to set email alerts
|

Small RNA Profiling of Influenza A Virus-Infected Cells Identifies miR-449b as a Regulator of Histone Deacetylase 1 and Interferon Beta

Abstract: The mammalian antiviral response relies on the alteration of cellular gene expression, to induce the production of antiviral effectors and regulate their activities. Recent research has indicated that virus infections can induce the accumulation of cellular microRNA (miRNA) species that influence the stability of host mRNAs and their protein products. To determine the potential for miRNA regulation of cellular responses to influenza A virus infection, small RNA profiling was carried out using next generation s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 57 publications
4
28
0
Order By: Relevance
“…IAV downregulates HDAC1 expression at both the mRNA and the polypeptide level. The reduction in HDAC1 mRNA level in IAVinfected cells observed here is consistent with a recent microarraybased gene expression profiling study (38). By using mainly a luciferase reporter assay and quantitative real-time PCR, Buggele et al (38) demonstrated that IAV induces host microRNA, miR449b that targets the 3= untranslated region of HDAC1 mRNA, and when added exogenously, miR-449b further reduced HDAC1 mRNA level in infected cells.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…IAV downregulates HDAC1 expression at both the mRNA and the polypeptide level. The reduction in HDAC1 mRNA level in IAVinfected cells observed here is consistent with a recent microarraybased gene expression profiling study (38). By using mainly a luciferase reporter assay and quantitative real-time PCR, Buggele et al (38) demonstrated that IAV induces host microRNA, miR449b that targets the 3= untranslated region of HDAC1 mRNA, and when added exogenously, miR-449b further reduced HDAC1 mRNA level in infected cells.…”
Section: Discussionsupporting
confidence: 90%
“…The reduction in HDAC1 mRNA level in IAVinfected cells observed here is consistent with a recent microarraybased gene expression profiling study (38). By using mainly a luciferase reporter assay and quantitative real-time PCR, Buggele et al (38) demonstrated that IAV induces host microRNA, miR449b that targets the 3= untranslated region of HDAC1 mRNA, and when added exogenously, miR-449b further reduced HDAC1 mRNA level in infected cells. However, they did not determine HDAC1 polypeptide level in response to the direct IAV infection and could not establish a direct anti-IAV role of miR-449b or HDAC1 since the depletion or overexpression of miR-449b did not have an effect on IAV infection (38).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…miRs cause degradation of target mRNAs through perfect and imperfect complementation between a seed sequence in the miR and target sequences, typically located within the 3=UTR or sometimes the 5=UTR of the target mRNA (39). Some miRs directly target viral mRNAs, while others act indirectly via cellular genes that in turn impact viral gene expression (40)(41)(42)(43). For example, miR-155 inhibits Epstein-Bar virus (EBV) lytic infection and plays a role in maintenance of latency (44), miR-498 and miR-330d reduce Kaposi's sarcoma-associated herpesvirus (KSHV) replication by targeting the viral RTA (43,45), and miR-100 and miR-101 attenuate HCMV replication via the mTOR pathway (41).…”
mentioning
confidence: 99%
“…In addition, microRNAs (miRNAs) have been found to play important roles in the virus life cycle. It has been confirmed that miRNAs can modulate the influenza virus life cycle by directly repressing viral protein expression or controlling the host immune response (Buggele et al, 2013;Song et al, 2010). In return, it has been reported that many viruses have adapted strategies to eliminate miRNAs harmful for their replication (Andersson et al, 2005;Lu & Cullen, 2004;Marcinowski et al, 2012).…”
Section: Introductionmentioning
confidence: 98%